2021
DOI: 10.1002/gcc.22971
|View full text |Cite
|
Sign up to set email alerts
|

Optical genome mapping, a promising alternative to gold standard cytogenetic approaches in a series of acute lymphoblastic leukemias

Abstract: Acute lymphoblastic leukemias (ALL) are characterized by a large number of cytogenetic abnormalities of clinical interest that require the use of several complementary techniques. Optical genome mapping (OGM) is based on analysis of ultra-high molecular weight DNA molecules that provides a high-resolution genome-wide analysis highlighting copy number and structural anomalies, including balanced translocations.We compared OGM to standard techniques (karyotyping, fluorescent in situ hybridization, single nucleot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
59
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(85 citation statements)
references
References 27 publications
(52 reference statements)
5
59
0
5
Order By: Relevance
“…16,18 Following this finding the OGM analytical soft- this study. 16,18 Moreover, Lestringant et al also reported cross-contamination between samples, a problem we did not encounter. 16 Besides potentially missing important alterations, OGM sometimes also provides false-positive results.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…16,18 Following this finding the OGM analytical soft- this study. 16,18 Moreover, Lestringant et al also reported cross-contamination between samples, a problem we did not encounter. 16 Besides potentially missing important alterations, OGM sometimes also provides false-positive results.…”
Section: Discussionmentioning
confidence: 80%
“…Discordances were seen in 3 cases where there was a gain or loss of an almost entire haploid/diploid set (changes in ploidy). In 2 cases with low hypodiploidy (12,16), the chromosomal gains were correctly identified by OGM but the results were incorrectly interpreted as hyperdiploid (Table 2). The OGM software allows you to manually plot the zygosity states of all the SVs (using filter set B, described in Supplementary Methods (Data S1) section, on the "De Novo Assembly" data), chromosome per chromosome.…”
Section: Concordance To Identify Aneuploidymentioning
confidence: 99%
“…With the aim to test the feasibility of OGM in the genetic classification of pediatric ALL, we selected genetically well-characterized ALL samples, which were intensively analyzed by well-established technologies (SNP-array, RNA-Seq, FISH, karyotyping, MLPA) used within our routine diagnostic workflow. Recently, it was shown that OGM may have the potential to be a routine tool in malignant hematology [24]. We show here for the first time that OGM allowed the detection of all chromosomal stratification-relevant genomic markers in ALL, including translocations, aneuploidies, and copy number profiles including IKZF1 plus in a retrospective as well as in a prospective manner.…”
Section: Discussionmentioning
confidence: 70%
“…The detection resolution for SVs mainly depends on the label distribution (~15 labels/100 kb) and can be as low as some hundred bp due to the calculation of label distances. A limitation of OGM is the detection of whole arm translocations (Robertsonian translocations) and SVs located in telomeric regions due to the absence of labels in these regions Depending on the amount of data generated (up to 4000 Gb), detection of SVs with allele frequencies below 10% may be possible [24]. Similar to observations by Lestringant et al, we were not able to detect CRLF2/P2RY8 fusions in patients #2 and #5 because of subclonality (#2) and the repetitive nature of the PAR region at Xp22.33 [24].…”
Section: Advantages and Limitations Of Ogmmentioning
confidence: 99%
See 1 more Smart Citation